A família Myrtaceae na reserva particular do patrimônio natural da Serra do Caraça, Catas Altas, Minas Gerais, Brasil - Morais, Patrícia Oliveira; Lombardi, Julio Antonio [UNESP] (My University, 2006)
This is a floristic survey of Myrtaceae in the Serra do Caraça, Minas Gerais. Fifty two species were found belonging to 12 genera - Myrcia with 17 species, Eugenia with nine, Campomanesia and Myrciaria with five species each, Psidium with four, Siphoneugena with three, Blepharocalyx, Calyptranthes, Marlierea and Myrceugenia with two species each, and Accara and Plinia with one species each. Descriptions of the genera and species, identification keys, geographical distributions, illustrations and comments are provided. © 2005 Instituto de Ciências Biológicas - UFMG.
The family Myrtaceae in the reserva particular do patrimônio natural da Serra do Caraça, Catas Altas, Minas Gerais, Brazil
Keywords: Minas Gerais; Myrtaceae; Serra do Caraça; Taxonomy; community composition; dicotyledon; floristics; identification key; phytogeography; taxonomy; Brazil; Serra do Caraca; South America; Blepharocalyx; Calyptranthes; Campomanesia; Marlierea; Myrceugenia; Myrcia; Myrciaria; Plinia; Psidium; Siphoneugena